City and modernity: Imaginary and aristoctatic mith - Cuadra Rojas, Álvaro (2017)
The research work that we have set out for us wants to continue and deepen that hypothesis, inspired by the writings of Walter Benjamin, which we have already explored in a recent publication, namely: The emergence of an early modernity, as a mutation of ethos in societies Bourgeois during the second half of the 19th century.